Effect of process parameters on quality of cold spinned tube head - Wardoyo, T.; Izman, S.; Kurniawan, Denni (2013)
Metal spinning can be used to produce hollow, axially symmetric sheet metal parts with low tooling and production costs, high flexibility, and low waste. Spinning parameters determine the quality of the spinned parts and are of interest for enabling the spinning of thick sheet metals. In this study, conventional metal spinning was conducted on a 6 mm thick low carbon steel with process below its recrystallization temperature to fabricate tube head, requiring maximum deflection of about 90°C at its edge. Spinning parameters varied were temperature (at room temperature and 300°C),feed (2 mm and 5 mm), and spinning speed (200 rpm and 250 rpm). Evaluation was made on the resulted surface morphology, thickness variation, and further analysis on hardness and microstructure of the spinned tube head. The resulted tube heads were of acceptable quality in terms of surface morphology and thickness variation, while hardness and microstructure analysis showed that inner parts of the workpiece were not affected by the spinning process. © (2013) Trans Tech Publications, Switzerland.